The yeasts Rho1p and Pkc1p regulate the transport of chitin synthase III (Chs3p) from internal stores to the plasma membrane - Valdivia, Raphael H. (National Academy of Sciences, 2003)
During cell stress, Saccharomyces cerevisiae increases the synthesis of chitin and glucans to strengthen and repair the cell wall. In this study, we show that under conditions of cell stress, the steady-state localization of chitin synthase III (Chs3p) shifts from internal stores (chitosomes) to the plasma membrane (PM). This redistribution occurs rapidly and requires the activators of the cell wall stress response signaling pathway, the G protein Rho1p, and the protein kinase Pkc1p, but not the cell integrity response mitogen-activated protein kinase cascade. Furthermore, expression of activated forms of Rho1p or Pkc1p, in the absence of cell stress, is sufficient to redistribute Chs3p to the PM. In cells deficient for both the clathrin adaptor complex 1 and Chs6p, where Chs3p is transported to the PM by an alternative bypass pathway, cell wall stress did not cause mobilization of Chs3p, suggesting that Rho1p/Pkc1p regulate Chs3p exit from the trans-Golgi network. The mobilization of an intracellular reservoir of Chs3p presents a novel opportunity to investigate the genetic basis of regulated vesicular traffic.